Long-term trends in the burden of pulmonary arterial hypertension in China and worldwide: new insights based on GBD 2021 - Xu, Zhehao; Ding, Jia; Liang, Ruiyun; Xie, Shuangfeng (Frontiers in Medicine, 2025)
BackgroundPulmonary arterial hypertension (PAH) poses a significant health challenge globally, with China experiencing a notable increase in its burden. Understanding the trends and factors contributing to PAH is crucial for developing effective public health strategies.MethodsThis study utilized data from the Global Burden of Disease (GBD) 2021 database to estimate the burden of PAH in China and worldwide from 1990 to 2021. A Bayesian age-period-cohort (BAPC) model was employed to analyze differences in PAH burden across age, gender, and time periods, and to project global epidemiological trends until 2036.ResultsFrom 1990 to 2021, the incidence and prevalence of PAH in China increased by 80.59% and 86.74%, respectively. The age-standardized incidence rate (ASIR) and age-standardized prevalence rate (ASPR) showed an annual percentage change (AAPC) of -0.07% and 0.25%, respectively. Conversely, the age-standardized disability-adjusted life year (DALY) rate and age-standardized mortality rate (ASMR) have been declining since 1990, with AAPC of -1.90% and -1.26%, respectively. Females and the 50–70 years age group experienced a higher PAH burden compared to males. Projections indicate that ASPR, ASMR, and age-standardized death rate (ASDR) will stabilize with minimal variation over the next decade.DiscussionThe findings highlight the age-related burden of PAH in China, particularly affecting older populations and women. The projected stabilization of PAH metrics over the next decade underscores the need for continued monitoring and targeted interventions. This study’s comprehensive analysis of PAH burden over three decades provides valuable insights for policymakers and healthcare providers, necessitating concerted efforts to address this critical health issue.